(untitled) (Teorías, Enfoques y Aplicaciones en las Ciencias Sociales, 2014)
This article generated from a phenomenological- hermeneutical investigation concluded (Barradas, 2013), in which it was proposed to derive interpretive theoretical elements of human development and approaches to econegocio as a green company, United Breweries Corporation, S.A. (DUSA), the Bolivarian Republic of Venezuela. The methodological condition developed in the interpretation of emerging subcategories from the following units: human development, and green econegocio company. This information was sought through the testimony focused on six social actors, however, for purposes of this article only refers to the findings derived from one social actor manager of this reality. Staff training, continuous improvement from the social benefits, values of solidarity and cooperation, mobilization ecological ethic as future business model, productive and economic side, constant innovation and international accreditation ISO 14001: In the framework of social construction of the categories identified and only green company in Venezuela, this in relation to the events of significance associated with the phenomenon of study. The reflections project to the attention of the business cluster to open production scenarios can be identified with econegocio, to monitor the ethical sense of internal organizational behavior conglomerate with a system of balanced relations in sustaining ecosystems and the social benefits.